Innovation in Islamic finance: Review of organized banking Tawarruq - Dewaya, Muhammad Abdullah (Review of Islamic Social Finance and Entrepreneurship, 2024)
Purpose – This research aims to discuss innovation in Islamic finance and banking products by analyzing organized banking Tawarruq as a sample of innovation. Innovation in Islamic finance is to provide Sharī῾ ah-compliant solutions for the actual needs of the industry. Studying organized banking Tawarruq was essential because it was a practical solution for cash financing as an alternative to ribā-based loans. This approach helped identify the challenges and opportunities for the development of Sharī῾ah structures and set innovation boundaries, goals, and impacts. Methodology – This is an analytical qualitative study. It analyzed contemporary research papers from three major markets: Indonesia, Malaysia, and the GCC. The focus was on organized Tawarruq because its innovation was for liquidity and cash purposes, which is a vital matter for financing and a challenge for Islamic banks. Findings – The organized Tawarruq and international Commodity Murābaḥah detailed applications may vary in different regions. There have been attempts to improve these shortcomings and provide a remedy to Sharī῾ah non-compliance. Standardizing pragmatic filters to avoid non-Sharī῾ah compliance and focus on moral and ethical guidelines is necessary to preserve the growth and reputation of Islamic finance. Integrating Islamic finance and Islamic social finance can create new opportunities for socially responsible innovations.Implications – These calls for Islamic banks to invest more in innovation. Create R&D funds to provide innovative, viable, and Sharī῾ah compliant liquidity solutions. Originality – Evaluating the organized Tawarruq and commodity Murābaḥah from an innovation perspective is a unique approach to learn from existing shortcomings and avoid reproducing the same mistakes.